Engineering high-spin state cobalt cations in spinel zinc cobalt oxide for spin channel propagation and active site enhancement in water oxidation - Sun, Yuanmiao (2022)
Spinel zinc cobalt oxide (ZnCo2 O4 ) is not considered as a superior catalyst for the electrochemical oxygen evolution reaction (OER), which is the bottleneck reaction in water-electrolysis. Herein, taking advantage of density functional theory (DFT) calculations, we find that the existence of low-spin (LS) state cobalt cations hinders the OER activity of spinel zinc cobalt oxide, as the t2g 6 eg 0 configuration gives rise to purely localized electronic structure and exhibits poor binding affinity to the key reaction intermediate. Increasing the spin state of cobalt cations in spinel ZnCo2 O4 is found to propagate a spin channel to promote spin-selected charge transport during OER and generate better active sites for intermediates adsorption. The experiments find increasing the calcination temperature a facile approach to engineer high-spin (HS) state cobalt cations in ZnCo2 O4 , while not working for Co3 O4 . The activity of the best spin-state-engineered ZnCo2 O4 outperforms other typical Co-based oxides.